Wanted: An Exegetical Realism - Minear, Paul Sevier (Theology today, 2002)
In many ways, nonverbal as well as verbal, the New Testament gives a confident witness to the realities (some invisible, some visible) of God's action in creating a new heaven and a new earth. Exegesis of these texts should therefore focus on understanding those realities, even in spite of the many inherent difficulties. To explore both the opportunities and the difficulties, texts are selected from the Epistle to the Hebrews, the Apocalypse of John, the Second Epistle to the Corinthians, and the Gospel of Matthew.